REÚSO DE ÁGUAS CINZAS EM LOTES URBANOS: USO DE SISTEMAS CONSTRUÍDOS DE ÁREAS ALAGADAS - Oliveira, Pedro; Ilha, Marina; Cruz, Luana (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The sustainable use of water in cities implies different measures for mitigating the impact of the need of potable water and the consequent sewage generation in buildings. Thus, strategies for water reuse assume great importance, together with adequate systems for the effluents treatment. Constructed wetlands are increasingly used for sewage treatment. However, these systems usually have large dimensions, since the retention time is determinant for their performance, making their use in urban lots unfeasible. This article presents a compilation of studies of constructed wetlands, verifying the effectiveness of the treatment, comparing the influence of the typology and associated technologies, and if the minimum quality levels for restricted reuse for non-potable activities are reached. The results indicated that the vertical typology, in most cases, reached better levels of the removal of organic load and total suspended solids.